Readability of amplitude modulation (AM) transmitter and receiver laboratory manual / Mohd Shahrul Ridzuan Zana Abidin - Zana Abidin, Mohd Shahrul Ridzuan (2012)
Engineering students in university generally have laboratory session which is related with their subject in that particular semester. UiTM FKE Communication students are all required to par take a laboratory session regarding AM transmitter and receiver. A study by Mohamad and Hamizan (2011) suggest that many students fail to understand the laboratory manual. In the research, a 15 items questionnaire was developed and administered to 66 Electrical Engineering (Communications) students. Further analysis indicates that many students not read the laboratory manual prior to laboratory sessions. In addition, the results indicate that 49.5% of student that did read the manual but failed to understand the lab sheet instructions. Both parametric and non-parametric analyses have yield unequal distribution in reading and understanding the lab sheet, thus implying a disparity in distribution between reading and understanding the lab sheet. Following this, there are ongoing efforts to improve the current AM transmitter and receiver lab sheet. Previous research indicate that the lack of procedure, the structure of the manual lab and the complexity of the words or phrase using in manual are the main factor students don't seem to understand the lab. By using readability software's, the readability factor can be identified. It is hoped that with review made on the manual, the student will find it easier to read and understand the laboratory as a whole.